New Guinean Issidae: description of new taxa in a poorly known island fauna (Hemiptera, Fulgoroidea) - Gnezdilov, V. M.; Cesne, M. Le; Soulier-Perkins, A.; Bourgoin, T. (Zootaxa, 2015)
In the framework of the recent expedition results of “Our Planet Reviewed Papua-New-Guinea 2012–2013” we provide here the first Issidae (Hemiptera, Fulgoroidea) fauna review of New Guinea with the description of three new taxa: one new genus Papunega Gnezdilov et Bourgoin gen. nov. with two new species: Papunega magnifacies Gnezdilov et Le Cesne, sp. nov. (type species), Papunega armocula Gnezdilov et Soulier-Perkins, sp. nov. Tetrica fasciatifrons Melichar, 1906 is transferred to the genus Papugena gen. nov. to become Papugena fasciatifrons (Melichar, 1906) comb. nov. New Guinean Issidae fauna now includes 7 genera and 16 species.